Nucleotide sequence diversity at the alcohol dehydrogenase 1 locus in wild barley (ıt Hordeum vulgare ssp. ıt spontaneum): an evaluation of the background selection hypothesis - Michael P. Cummings; Clegg, M. T. (Proc Natl Acad Sci USAProc Natl Acad Sci USA, 1998)
The background selection hypothesis predicts a reduction in nucleotide site diversity and an excess of rare variants, owing to linkage associations with deleterious alleles. This effect is expected to be amplified in species that are predominantly self-fertilizing. To examine the predictions of the background selection hypothesis in self-fertilizing species, we sequenced 1,362 bp of adh1, a gene for alcohol dehydrogenase (Adh; alcohol:NAD+ oxidoreductase, EC 1.1.1.1), in a sample of 45 accessions of wild barley, Hordeum vulgare ssp. spontaneum, drawn from throughout the species range. The region sequenced included 786 bp of exon sequence (part of exon 4, all of exons 5-9, and part of exon 10) and 576 bp of intron sequence (all of introns 4-9). There were 19 sites polymorphic for nucleotide substitutions, 8 in introns, and 11 in exons. Of the 11 nucleotide substitutions in codons, 4 were synonymous and 7 were nonsynonymous, occurring uniquely in the sample. There was no evidence of recombination in the region studied, and the estimated effective population size (Ne) based on synonymous sites was approximately 1.8-4.2 x 10(5). Several tests reveal that the pattern of nonsynonymous substitutions departs significantly from neutral expectations. However, the data do not appear to be consistent with recovery from a population bottleneck, recent population expansion, selective sweep, or strong positive selection. Though several features of the data are consistent with background selection, the distributions of polymorphic synonymous and intron sites are not perturbed toward a significant excess of rare alleles as would be predicted by background selection.